Service Strategy and Implementation of Digital Sharia Pawnshops in Increasing the Number of Customers in Rantau Prapat - Ade Rizki Meilani; Nur Mija Hasibuan; Muhammad Lathief Ilhamy Nasution (Penerbit Jurnal Indonesia, 2022)
Pledge as one of the categories of debt-receivable agreements, for the trust of the lender, the debt holder swears merchandise as collateral for obligations. The collateral remains the property of the person who pledged it, but is limited by the recipient of the votive. The special functional components of sharia second-hand shops can be completed by Islamic financial institutions, especially sharia second-hand shops, both as private and government organizations. Improvements are currently accelerating, this is evidenced by progress in various fields, especially innovation. However, not all innovations provide accommodation and positive effects for their clients if they are not handled as expected. This study plans to determine the degree of business administration system for the Digital Sharia Pawnshop application (PSD) in supporting exchanges and increasing potential in facing competition, and to determine the adequacy of online administration carried out by Rantau Prapat Syariah Pegadaian through the Digital Sharia Pawnshop Application (PSD) in expanding the number of customer. Discussion of exam results using a graphical methodology. From the results of this review, it shows that with the implementation of a sophisticated sharia second-hand shop (PSD) application, it is very easy for the general public to make transactions at sharia second-hand shops. So the Digital Sharia Pawnshop (PSD) for this situation sharpens the organization's special value in facing competition. The effectiveness of PSD is reviewed through 7 dimensions, namely efficiency, reliability, compliance, service privacy, responsiveness, compensation, and contact.